Unemployment and Right-wing Extremist Crime - Armin Falk; Andreas Kuhn; Josef Zweimüller (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2009)
It is frequently argued that unemployment plays a crucial role for the occurrence of right- wing extremist crimes. We empirically test this hypothesis using data from Germany. We find that right-wing criminal activities occur more frequently when unemployment is high. The big difference in right-wing crime between East and West German states can mostly be attributed to differences in unemployment. This finding reinforces the importance of unemployment as an explanatory factor for right-wing crime and questions explanations based solely on the different socialization in former communist East Germany and the liberal West German states.
Keywords: J15; J69; K42; 330; Hate crime; right-wing extremism; unemployment; cost of unemployment